THE UNITY OF SCIENCE PARADIGM, CHALLENGES, AND SOLUTIONS IN PANDEMIC ERA - Wijaya, Mirza Mahbub (UIN Sunan Kalijaga Yogyakarta, 2021)
This study has a background on the problem of the COVID-19 pandemic problem that is being faced by Indonesian people, even include many countries in the world. The urgency of this research is to provide literacy or a new paradigm of scientific integration. This is because Muslims are very difficult to solve contemporary problems in various aspects up to the current pandemic era. The method used in this research is a descriptive-analytical method with a philosophical and phenomenological approach. Researchers offer a new perspective with the humanization of Islamic sciences that can be applied in the pandemic era. For example, the humanization of jurisprudence and the humanization of Islamic Theology. Thus the new paradigm offered in responding to all humanitarian problems, including the COVID-19 pandemic, can be a solution.